Analysis of Science Learning Process by Using Learning Module of Character Education Oriented through Quantum Learning Approach - Sari, Rona Taula; Jusar, Ira Rahmayuni (Jurnal Penelitian dan Pembelajaran IPA, 2018)
The process of science learning is very influential on students’ understanding. Uncertainty of students on various materials of science can cause various obstacles, such as students’ difficultyon understanding thelinkage material, as the result, unsuccesful on achieving the expected learning objectives. Efforts to improve the students’ understanding in learning process in order to avoid poor performance of student learning by using learning modules character educationoriented through Quantum Learning approach. The purpose of this research is to know the process of science learning by using learningmodule of character educationoriented through quantum learning approach on digestive system course in grade 5 at one of primary school at Padang, Indonesia. The type of this research is descriptive research. Data related to the implementation of learning derived from the process of science learning in the form of recording the learning process, interview guides, questionnaires and observation sheet on the implementation of learning. Data collection techniques refer to teacher performance appraisal instrument-2 (IPKG-2). Based on the result of the research, it can be concluded that the implementation of learning has not been referring to IPKG-2, but it has reached very good criteria (3.61) in grade 5 at one of primary school at Padang, Indonesia